2013
DOI: 10.1681/asn.2012080855
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hypoxia Responses in Renal Tissue

Abstract: pO 2 in the kidney is maintained at relatively stable levels by a unique and complex functional interplay between renal blood flow, GFR, O 2 consumption, and arteriovenous O 2 shunting. The fragility of this interplay makes the kidney susceptible to hypoxic injury. Cells in the kidney utilize various molecular pathways that allow them to respond and adapt to changes in renal oxygenation. This review provides an integrative perspective on the role of molecular hypoxia responses in normal kidney physiology and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 31 publications
3
124
2
3
Order By: Relevance
“…In our study, HIF-1a was induced during hypoxic incubation of RPTCs, starting from 3 hours and lasting until 9 hours (Figure 2A). In line with previous work, [32][33][34] HIF-1a was also induced in kidney tissues during renal ischemia-reperfusion in our study ( Figure 2B). …”
Section: Hif-1 Contributes To Mir-489 Induction In Ischemic Aki and Hsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, HIF-1a was induced during hypoxic incubation of RPTCs, starting from 3 hours and lasting until 9 hours (Figure 2A). In line with previous work, [32][33][34] HIF-1a was also induced in kidney tissues during renal ischemia-reperfusion in our study ( Figure 2B). …”
Section: Hif-1 Contributes To Mir-489 Induction In Ischemic Aki and Hsupporting
confidence: 94%
“…32,38,39 However, it remains unclear as to which HIF-1-regulated genes are critical to the regulation. In addition to the classic genes that facilitate oxygen delivery, angiogenesis, and anaerobic metabolism or glycolysis, 31,33 recent studies have documented HIF-1 regulation of miRs, such as miR-210, miR-21, miR-29, and miR-127. 25,[40][41][42] This study has further shown miR-489 induction via HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can be explained by irreversible damage at the cellular level, where mitochondria are injured and the electron transfer chain is inhibited (Wang et al, 2004). Cells of the proximal convoluted tubules are very sensitive to hypoxia, which leads to their dysfunction (Haase, 2013). On the other hand, the impact of cadmium on lysosomes, despite its multiplexing, can lead to lysosomal membrane destabilisation, resulting in an efflux of lysosomal enzymes into body fluids (blood, urine) (Fotakis et al, 2005;Thomas et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…1 1 cells, that suppress the excessive activation of endothelial cells and neutrophil infiltration in IRI kidneys. 2 Neutrophil infiltration occurs in ischemic kidneys within the early few hours of reperfusion, which has primarily been demonstrated in experimental models. 3 Neutrophils exacerbate ischemic injury through blockage of capillaries (no-reflow phenomenon), release of reactive oxygen species and inflammatory cytokines including IFN-g and IL-17, and disrupting the endothelial and epithelial barriers during their transmigration into the interstitial compartment.…”
Section: Disclosuresmentioning
confidence: 99%
“…1 Hence, molecular mechanisms and consequences of impairment of renal oxygenation have been the focus of intense research interest in both acute and chronic kidney injury, and opportunities for therapeutic targeting of hypoxia to retard or even prevent kidney disease progression have been proposed. 2 However, insights into how a broad spectrum of renal injuries may cause peritubular microvascular rarefaction and renal hypoxia remain remarkably limited, considering the postulated preeminent role of tissue hypoxia in particular in tubulointerstitial fibrosis and kidney disease progression.…”
mentioning
confidence: 99%